Peran Kualitas Pelayanan Frontliner, Mobile Banking dan Kepercayaan Terhadap Kepuasan Nasabah - Lailatul Kamilah Arifin; Ahmad Majdi Tsabit (Univiversitas Dr. Djar Wattiheluw, 2023)
The purpose of this study was to test and analyze the impact of frontliner service quality, mobile banking, and trust on customer satisfaction of BSI KCP Sumenep. This study uses a quantitative approach with a sample size of 100 respondents. The analytical tool used is multiple linear regression analysis which is preceded by a description of the research data, validity and reliability tests, classical assumption tests, and hypothesis testing. Data processing is done by utilizing the SPSS statistic 26 program. The results showed that the variable service quality of frontliner services, mobile banking, and trust partially and simultaneously had a positive and significant impact both partially and simultaneously on customer satisfaction BSI KCP Sumenep.